Comprehensive measurement of respiratory activity in permeabilized cells using extracellular flux analysis - Salabei, Joshua K. (2014)
Extracellular flux (XF) analysis has become a mainstream method to measure bioenergetic function in cells and tissues. While this technique is commonly used to measure energetics in intact cells, we outline here a detailed XF protocol for measuring respiration in permeabilized cells. Cells are permeabilized using saponin, digitonin, or recombinant perfringolysin O (XF PMP reagent) and provided with specific substrates to measure complex I- or II-mediated respiratory activity, Complex III+IV respiratory activity, or Complex IV activity. Medium- and long-chain acylcarnitines or glutamine may also be provided for measuring fatty acid oxidation or glutamine oxidation, respectively. This protocol allows for such measurements using a minimal number of cells compared with other protocols, without the need for mitochondrial isolation. The results are highly reproducible, and mitochondria remain well coupled. Collectively, this protocol provides comprehensive and detailed information regarding mitochondrial activity and efficiency, and, following preparative steps, takes approximately 6 hours to complete.